2023
DOI: 10.1111/1541-4337.13248
|View full text |Cite
|
Sign up to set email alerts
|

Virtual, augmented, and mixed reality as a versatile tool in food consumer behavior evaluation: Recent advances in aroma, taste, and texture incorporation

B Bhavadharini,
V Monica,
R Anbarasan
et al.

Abstract: The perceptual behavior of consumers on a product displayed in the market has a vital role in analyzing the importance given to that product. Therefore, various strategies have been developed to understand this consumer behavior in the selection of products. Immersive technologies like virtual, augmented, and mixed reality are among them. With the foremost feature of immersion in the virtual world and interaction of users with virtual objects, virtual reality, and augmented reality have unlocked their potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 186 publications
0
1
0
Order By: Relevance
“…The principle of multisensory integration for enhancing saltiness is achieved through the synergy between taste and smell, which occurs in several brain regions, including the anterior insula, frontal cortex, anterior cingulate cortex, and prefrontal cortex of the eye sockets ( Barry, Danielle, Samuel, & Juyun, 2012 ; Bhavadharini, Monica, Anbarasan, & Mahendran, 2023 ). Previous research has confirmed that odors with savory properties, such as ham, Comté cheese, sardine, and soy sauce aroma could significantly enhance saltiness perception ( Chen et al, 2024 ; Lawrence, Salles, & Palicki, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The principle of multisensory integration for enhancing saltiness is achieved through the synergy between taste and smell, which occurs in several brain regions, including the anterior insula, frontal cortex, anterior cingulate cortex, and prefrontal cortex of the eye sockets ( Barry, Danielle, Samuel, & Juyun, 2012 ; Bhavadharini, Monica, Anbarasan, & Mahendran, 2023 ). Previous research has confirmed that odors with savory properties, such as ham, Comté cheese, sardine, and soy sauce aroma could significantly enhance saltiness perception ( Chen et al, 2024 ; Lawrence, Salles, & Palicki, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Balasubramanian and Konar (2022) investigate the prospects of an AR-integrated menu in producing a healthy dining experience with nutritional information as well as a realistic/immersive dining pace. Bhavadharini et al (2023) explored how augmented and mixed reality affects consumer food choices, leading to new product development, real-time shopping insights, and an understanding of emotional influences on product selection. Styliaras (2021) study explores the current utilization of augmented reality applications in the food analysis and promotion sectors through products and orders.…”
Section: Introductionmentioning
confidence: 99%